Leptomeningeal metastasis from cervical cancer: Report of two cases and a review of the literature. Issue 8 (17th May 2021) - Omori, Makiko; Ogawa, Tatsuyuki; Oyama, Keisuke; Tagaya, Hikaru; Fukasawa, Hiroko; Hirata, Shuji
Abstract: Leptomeningeal metastases from cervical cancer are extremely rare, with only 24 cases reported in the English‐language literature. Leptomeningeal metastasis (LM) is usually a late event, but it can develop at any stage. A 44‐year‐old woman presented with vertigo, tinnitus, diminution of hearing, and a cervical tumor at the initial visit. She underwent whole brain radiotherapy and systemic chemotherapy. Five months after the initial visit, her condition deteriorated rapidly and she died. A 49‐year‐old woman underwent surgery and pelvic radiotherapy for cervical cancer. She underwent resection of lung metastases 2 years later and received systemic chemotherapy for lymph node metastases 4 years later. Five years after the initial visit, the patient suddenly presented with diplopia, headache, and vomiting; her clinical course was fulminant and she died. Most patients with LM present with diverse clinical manifestations and deteriorate rapidly despite multiple treatment modalities. Gynecologic oncologists should be aware of this rare complication.